Conceptualizing Illness: Nodding Syndrome in Northern Uganda - van Bemmel, Karin (Afrika Focus, 2020)
This paper presents an ethnographic study of conceptualizations of nodding syndrome (NS) in Uganda. NS is a poorly understood condition characterized by repetitive nodding of the head, mental retardation and stunted growth, which affects thousands of children in northern Uganda, South Sudan and Tanzania. Although extensive research for causative agents has been conducted, no convincing single cause has been reported. This study establishes an understanding of different representations of NS and argues that the episodes of head nodding are related to the socio-political body in which they are manifested. Three interwoven approaches towards NS take main stage whereby the syndrome is presented as a biomedical, spiritual and/or political problem. The conceptualizations are linked to different notions of healing and affected families combine various forms of therapy. Through the examination of different narratives, this study disrupts the idea of a singular perspective on illness and pleads for a focus on motion and plurality. KEY WORDS: NODDING SYNDROME, UGANDA, HEALTH, CONCEPTUALIZATION, ANTHROPOLOGY